Analisis Kesulitan Siswa dalam Menyelesaikan Soal Cerita pada Materi Sistem Persamaan Linear Dua Variabel di SMA ST Alfonsus Weetebula - Kalembu, Stefania Sulastri; Lede, Yulius Keremata; Napu, Timotius Woda; Lubur, Dorothea Novia Ludo (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The second research aims to identify the types of difficulties and to determine the factors causing student difficulties. The type of research used is qualitative descriptive. This research was conducted at SMPK Flos Karmeli in the second semester of the 2024/2025 academic year with 28 students as the research subjects. The data collection techniques used in this research are written tests, interviews, and documentation. The data analysis technique used is qualitative data analysis with stages of data reduction, data presentation, and drawing conclusions. The research results show that the errors are divided into 3 parts, namely Verbal problem difficulty 44.73%, Conceptual difficulty 69.73%, and principle difficulty 89.47%. (1) Verbal problem difficulty occurs when students are not accurate in translating into a Mathematical model, students are not accurate in using the data that will be used, and students are not accurate in drawing conclusions; (2) Conceptual difficulty occurs when students cannot write down what is known and what is being asked, students are confused in representing the problems, for example, a notebook is represented as X and a pencil is represented as y; and (3) Principle difficulty occurs when students are not accurate in using arithmetic operations, and students do not complete the calculations.